ANALISIS FAKTOR.FAKTOR YANG MEMPENGARUHI KOEFISIEN RESPON LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEJ - Noviyanti Tiolemba; Erny Ekawati (Jurnal Riset Akuntansi dan Keuangan, 2008)
\h;;;"d, is an empirical one wlnse purposes are to prove is beta risk; leverage, earning growth std size has intluence on to earnings response coeficient. Sampk which are used on this sntdy are 390 data of mmufacturing corporations in Indonesig. Ihe period of study is 1995-2004. There are two models used, first model to determining earnings response coefficient and second rnodel to testing factors which in/luence euningsresponse coefficient. Stotistic models which ue used are multipleregressions.  The results are beta has negative effect on earnings response coefiicient, leverage has negative efiect on earnings response coefficient, eorning growth has positive inJluences to the earnings response coefficient atter being controlled by other variable and size has negative effect on eunings response coeficient.Kqtwords: Earnings Response Coeficient (ERC), Return, Unexpected Earning Per Share